IDENTIFICATION OF EURYTREMA SPP. IN BRAHMAN CROSS CATTLE SLAUGHTERED IN BANDA ACEH SLAUGHTERHOUSE - Savira, Filza; Hanafiah, Muhammad; Helmi, Teuku Zahrial (Buletin Veteriner Udayana, 2023)
Eurytrema spp. is a trematode worm that generally attacks the pancreas of livestock and humans which can cause chronic interstitial pancreatitis, weight loss that leads to decreased livestock productivity and ends in death. The purpose of this study is to identify the parasitic worm Eurytrema spp. and also to find out the prevalence rate in Brahman Cross cattle slaughtered in Banda Aceh slaughterhouse. This study used a sample of 20 pieces of Brahman Cross cattle pancreas from the Banda Aceh slaughterhouse. The worms were collected by taking the pancreas of Brahman Cross cattle that had been cut and stained with the Semicon Carmine staining method. The parameters of this study were the morphological differences in size of the body, oral sucker, ventral sucker and reproductive organs in each species of Eurytrema spp. The results showed that out of the 10 worms found, there was only 1 species, namely E. pancreaticum , which has the characteristics of a wide body with a length of 8-16 mm, the oral sucker is larger than the ventral sucker and lobed testes and ovaries. The prevalence rate of infection with E. pancreaticum is 15%. It was concluded that the worm that infects the Brahman Cross cattle slaughtered in Banda Aceh slaughterhouse is E. pancreaticum .